(3eNJUQ cJGH GdYjfs - (3CHh YHO Gddg eMeO Hf YHO Gddg GdNWjH GdEScGais; (3GdNdjd Hf CMeO Hf YeQh Hf Jeje GdaQGgjOj GdCROj GdjMeOj, CHh YHO GdQMef,J (B170 (3g` s
(3ChdgG (B:s
(3cdGe GdYQH eHfi Ydi CQHYI GdKfGFi hGdKdGKi hGdQHGYi hGdNeGSi s
(3BNQgG (B:s
(3hbO CJjJ hGjGg ddTeS VhFgG Je cJGH GdGda hGdhGh hGdjG hgh BNQ cdGe GdYQH hddg GdMeO Je eNJUQ cJGH GdYjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B112s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1443s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs